Pengaruh Penerapan LKPD Berbasis PjBL terhadap Keterampilan Berpikir Kritis dan Hasil Belajar Kognitif Siswa - Ewi Suhendri; Titi Laily Hajiriah; Ida Royani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This pre-experimental study, utilizing a one-group pretest-posttest design, aimed to examine the validity and effectiveness of a Project-Based Learning (PjBL)-based Student Worksheet on the topic of environmental pollution regarding students' critical thinking skills and cognitive learning outcomes. The study population comprised all students at SMAN 8 Mataram, with class X MIPA 1 selected as the sample using a non-random sampling technique. Data were collected using instruments consisting of a critical thinking essay test (6 items), a cognitive multiple-choice test (12 items), and expert validation sheets. Data analysis employed Aiken’s V index for validity and the N-Gain formula to measure competency improvement. The results indicated that all materials fell into the